2018
DOI: 10.3892/ijmm.2018.3405
|View full text |Cite
|
Sign up to set email alerts
|

miR‑21‑5p confers doxorubicin resistance in gastric cancer cells by targeting PTEN and TIMP3

Abstract: Drug resistance and disease recurrence are major obstacles to the effective treatment of cancer, including gastric cancer (GC). However, the mechanisms of drug resistance remain to be fully elucidated. The present study investigated the roles of microRNA (miR)-21-5p in the doxorubicin (DOX) resistance of GC cells and the underlying mechanisms. miR-21-5p expression levels were identified to be inversely correlated with two well-known tumor suppressor genes, phosphatase and tensin homologue and tissue inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…MiR-20a was also proved to enhance gastric cancer resistance to ADR via inhibiting expression of early growth response 2 (EGR2), a member of a multi-gene family which encoding C2H2type zinc-finger proteins [60]. Through silencing PTEN and tissue inhibitor of matrix metalloproteinases 3 (TIMP3), miR-21-5p increases ADR resistance of gastric cancer cells [61]. It has also been found that miR-633 promotes ADR resistance of gastric cancer by inhibiting expression of Fas-associated death domain (FADD) [62].…”
Section: Mirnas and Adr Resistancementioning
confidence: 99%
“…MiR-20a was also proved to enhance gastric cancer resistance to ADR via inhibiting expression of early growth response 2 (EGR2), a member of a multi-gene family which encoding C2H2type zinc-finger proteins [60]. Through silencing PTEN and tissue inhibitor of matrix metalloproteinases 3 (TIMP3), miR-21-5p increases ADR resistance of gastric cancer cells [61]. It has also been found that miR-633 promotes ADR resistance of gastric cancer by inhibiting expression of Fas-associated death domain (FADD) [62].…”
Section: Mirnas and Adr Resistancementioning
confidence: 99%
“…In line with this common regulation, TIMP3 and PTEN were both implicated in miR-221/miR-222-mediated TRAIL resistance 41 and miR-21-5p-mediated doxorubicin resistance. 42 The critical role of PTEN in chronic liver diseases was recently demonstrated in vivo with Pten-null mice being more prone to develop progressive liver fibrosis and HSC activation than their wild type littermates. 43 In addition, PTEN The National Cancer Institute proliferation subtype (NCIP, low and high proliferation).…”
Section: Mir-21 Mir-221 and Mir-222 Are Markers Of Poor Prognosis mentioning
confidence: 99%
“…Increased expression levels of miR-494, miR-422a, miR-140, miR-103/107, and miR-16-1, and reduced levels of miR-501-5p and miR-21-5p promoted the chemosensitivity to DOX (for more details, refer to Table 3). [57][58][59][60][61][62][63][64] Among these, miR-103 and miR-107 were the only miRNAs demonstrated to have effects on resistance both in vitro and in vivo. 60 Another important miRNA that is taking the spotlight in chemotherapy resistance research is miR-21.…”
Section: Other Single-drug Resistancementioning
confidence: 99%
“…miR-21-5p targets PTEN to induce both DOX and DDP resistance. 30,48,64 Other studies showed that miR-21 targets P-gp to induce PTX resistance. 65 Notably, PTEN is not only a target gene of miR-21-5p but is also a target of miR-193-3p, miR-147, and miR-106a.…”
Section: Other Single-drug Resistancementioning
confidence: 99%
See 1 more Smart Citation